Four new species of Bauhinia sect. Pauletia and a new description of Bauhinia burchellii Bentham (Leguminosae) from Brazil - Vaz, Angela Maria Studart Da Fonseca; Lewis, Gwilym P. (Phytotaxa, 2015)
Four new species of Bauhinia sect. Pauletia ser. Cansenia from Brazil are described: Bauhinia funchiana, Bauhinia malmeana, Bauhinia piresii and Bauhinia uberlandiana. All four are trees or treelets lacking tendrils and prickles. Flowers are arranged in pairs in pseudoracemes, each flower has a tubular hypanthium over 1.5 cm long and a calyx that is lobed at anthesis.  In addition, the buds and flowers of B. burchellii are described for the first time.